(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Phrases are used to create a vivid and moving image of the story, the feelings of the characters and the themes of the story. They help the reader connect more deeply with the story and understand the characters’ experiences more fully. In the following article, an attempt is made to analyze expressions through some stories of Abdulla Kahhor.